(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article states that taxes are one of the main links of economic relations in society, as well as the main form of income of the state. The purpose of the article is to conduct the analysis of tax revenues to the state budget in order to determine the peculiarities of the functioning of the Ukrainian tax system and assess its fiscal efficiency. According to the results of the study of the Ukraine’s Consolidated Budget incomes dynamics, the tendency of their growth has been revealed. The structure of tax revenues is analyzed. The correlation between direct and indirect taxes in the tax system of Ukraine is investigated and their role in filling the state budget is determined. The analysis of the main taxes having the highest fiscal value was carried out. The volume of personal income tax revenues was investigated, the factors that influenced of their change were determined. The enterprise income tax has been analyzed, and its fiscal role in filling the consolidated budget of the state is determined. The main changes in the method of calculation and payment of these taxes, which influenced the dynamics of its revenues to the budget, are outlined. Indirect taxes, such as value-added tax (VAT) and excise tax, have the most important role in the formation of budget revenues. The article analyzes the impact of indirect taxes and determines the factors that influence the change in their volume. It is revealed that the current mechanism of VAT payment significantly reduces its fiscal efficiency, since more than half of the received tax returns to the payers. Therefore the main amount of VAT comes from taxation of imports. Despite this, VAT remains the most significant source of budget revenues. Its share in tax revenues of the consolidated budget increased throughout the period under investigation. In contradistinction to VAT, most of the excise tax comes from internal transactions with excisable goods. The analysis shows that the share of tax revenues in the consolidated budget is constantly fluctuating, which is a consequence of the imperfection of taxation in Ukraine, the constant changes in the structure of the tax system and the mechanism for collecting basic taxes, the general instability of the economic situation in the country. In general, when assessing the fiscal efficiency of the Ukrainian tax system, it can be stated that today the volume of taxes in Ukraine are quite high. In this context, an important task is to optimize the tax burden. Excessive and uneven tax burden in the country leads to a decrease in economic activity and its shadowing.